Lys 42/43/44 and Arg 12 of thrombin-activable fibrinolysis inhibitor comprise a thrombomodulin exosite essential for its antifibrinolytic potential - Wu, Chengliang; Stafford, Alan R.; Fredenburgh, James C.; Weitz, Jeffrey I.; Gils, Ann; Declerck, Paul J.; Kim, Paul Y. (Thrombosis and Haemostasis, 2017)
The thrombin-thrombomodulin (TM) complex activates thrombin-activable fibrinolysis inhibitor (TAFI) more efficiently than thrombin alone. The exosite on TAFI required for its TM-dependent activation by thrombin has not been identified. Based on previous work by us and others, we generated TAFI variants with one or more of residues Lys 42, Lys 43, Lys 44 and Arg 12 within the activation peptide mutated to alanine. Mutation of one, two, or three Lys residues or the Arg residue alone decreased the catalytic efficiency of TAFI activation by thrombin-TM by 2.4-, 3.2-, 4.7-, and 15.0-fold, respectively, and increased the TAFI concentrations required for half-maximal prolongation of clot lysis times (K1/2) by 3-, 4,- 15-, and 24-fold, respectively. Mutation of all four residues decreased the catalytic efficiency of TAFI activation by 45.0-fold, increased the K1/2 by 130-fold, and abolished antifibrinolytic activity in a clot lysis assay at physiologic levels of TAFI. Similar trends in the antifibrinolytic activity of the TAFI variants were observed when plasma clots were formed using HUVECs as the source of TM. When thrombin was used as the activator, mutation of all four residues reduced the rate of activation by 1.1-fold compared with wild-type TAFI, suggesting that these mutations only impacted activation kinetics in the presence of TM. Surface plasmon resonance data suggest that mutation of the four residues abrogates TM binding with or without thrombin. Therefore, Lys 42, Lys 43, Lys 44 and Arg 12 are critical for the interaction of TAFI with the thrombin-TM complex, which modulates its antifibrinolytic potential.
Keywords: TAFI; carboxypeptidase B2; thrombomodulin; fibrinolysis; kinetics